Management Information Systems on Integrated Student and Lecturer Data - Hendriyati, Penny; Agustin, Farida; Rahardja, Untung; Ramadhan, Tarisya (APTISI Transactions on Management (ATM), 2022)
One of the most important things in universities is the development of information systems and management of integrated data, important because of the high needs and completeness of attributes in each component related to academic affairs in all universities. Primary data in academics are students and lecturers. Data management and governance are well taken care of in order to deliver information to be accurate, transparency, accountability and actual. Lecturers and students can apply the SDLC model to produce a system that will later improve or replace the old system, through the design and implementation of data management information systems. In the application of policies towards lecturers and students, in this information system will provide formulation and overview to the leadership.